ChemInform Abstract: Easy Access to 1H‐Pyrrolo[3′, 4′:5, 6]pyrido[2, 3‐d]pyrimidine‐2, 4, 6, 8(3H, 7H)‐tetraone and Selectively N7‐Substituted Analogues Through Key Synthons. Issue 10 (February 2016) - Tourteau, Aurelien; Merlet, Eric; Bontemps, Alexis; Leland, Mathilde; Helissey, Philippe; Giorgi‐Renault, Sylviane; Desbene‐Finck, Stephanie
Abstract: For the synthesis of the title tetraone, the new synthon, pyrrole (VI), is developed and treated with 6‐amino‐uracil under mild reaction conditions.